Immigrant entrepreneurs in Malaysia: An exploratory study on their business success and prospects in small retail business - Abdullah, Moha Asri; Nel, Pieter; Melallieu, Peter; Mohd Thas Thakar, Mohamed Asmy (2016)
International migration is increasingly prevalent in the global economy. Research has, amongst others, included their social experiences, cultural and psychological perspectives. Little is however known about their involvement in small businesses in receiving countries. The literature tends to suggest that decisions of immigrant entrepreneurs’ involvement in small businesses are related to push and pull factors and their presence is viewed as having characteristics different from normal labour immigration. This paper highlights some issues and challenges of immigrant entrepreneurs and their business success and prospects in small retailing businesses in Kuala Lumpur in Malaysia. Based on 316 immigrant entrepreneurs surveyed it was found that the majority of immigrant entrepreneurs come from Bangladesh, Pakistan and Indonesia. The finding show that immigrant entrepreneurs are relatively well prepared for business and obtained experience before initiating a business. The inference analysis indicated immigrant entrepreneurs are positive about business issues as well as business success and prospects with highly significant relationship between those variables. The research concludes that immigrant entrepreneurs and their business activities can be a source of entrepreneurial development, employment generation and future impetus for economic growth in Malaysia. The results also open the way for comparisons with other countries which have immigrant entrepreneurs.